Gerard Justin Ferrari's Political Clay - Chilton, Galadriel (My University, 2006)
A presentation of works from sculptor Gerard Justin Ferrari's Gizmology series. Early works in the series were described as "political cartoons in the third dimension." More recent pieces embody raw anger rather than satire, and body parts rather than playful objects. With them, Ferrari illustrates a fragmented humanity brutalized by mega corporations and politics. For example, with its collage of body parts and technology, Inch of Soul (2000) addresses how contemporary media affects spiritual, psychological, and intellectual development.
Keywords: Art and Politics; Ferrari, Gerard Justin